Cortical Spreading Depression of Leao From Mitochondrial Function to Brain Metabolic Score (BMS) - Mayevsky, Avraham; Sonn, Judith (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book focuses on energy metabolism and brain functions related to Cortical Spreading Depression of Leao (CSD), an important issue in brain pathophysiology. The first part of the book offers a comprehensive overview of the history and early research on CSD, and then discusses the recent advances in the technology used to map and monitor brain mitochondrial NADH redox state and other physiological functions during CSD. The chapters explore the connection between CSD and mitochondrial function under hypoxia, Ischemia and various drugs treatment, and provide a resource to scientists researching the development of CSD during various brain pathophysiological conditions. This book is essential to scientists and students working in the field of bioenergetics of the brain and various organs and tissues in the body. The use of this technology is also crucial and applicable in the neuroscience field.
Aim of the book -- Basic principles and technology of nadh and multiparametric monitoring used in studying cortical spreading depression (csd) -- Single point and multisite monitoring of brain nadh fluorescence under csd -- Sequence of physiological responses recorded during induced csd event -- Spontaneous development of csd related to brain pathophysiological conditions -- The effects of brain metabolic and other perturbations on the responses to induced csd -- Effects of pharmacological agents on csd -- Clinical monitoring of csd in the human brain -- CSD and the lifenlight score (lls) -- Discussion and conclusions -- Index.
Keywords: Neurosciences; Bioenergetics; Biomedical engineering; Neurochemistry; Mental health; Neuroscience; Bioenergetics; Biomedical Engineering and Bioengineering; Neurochemistry; Mental Health